Hadith #2502 - Sunan Abi Dawud - Abu Umama bin Sahl; al-Qasim bin 'Abdur Rahman القاسم بن عبد الرحمن بن عبد الله; al-Waleed bin Muslim bin Shahab الوليد بن مسلم بن شهاب; Amr bin 'Uthman عمرو بن عثمان بن عفان; Yahya bin al-Harith al-Dhamari يحيى بن الحارث الذماري (Sunan Abi Dawud)
Abu Hurairah reported the Prophet (ﷺ) as saying “He who dies without having fought or having felt fighting (against the infidels) to be his duty will die guilty of a kind of hypocrisy.”
Grade: Sahih

Hadith #4679 - Sunan Abi Dawud - Abu Umama bin Sahl; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Mu'ml bin al-Fadl مؤمل بن الفضل; Muhammad bin Shu'aib bin Shabur محمد بن شعيب بن شابور; Yahya bin al-Harith al-Dhamari يحيى بن الحارث الذماري (Sunan Abi Dawud)
I did not see more defective in respect of reason and religion than the wise of you (women). A woman asked: What is the defect of reason and religion ? He replied: The defect of reason is the testimony of two women for one man, and the defect of faith is that one of you does not fast during Ramadan (when one is menstruating), and keep away from prayer for some days.
Grade: Sahih